A Randomized, Placebo-Controlled Clinical Trial of Famciclovir in Shelter Cats with Naturally Occurring Upper Respiratory Tract Disease - Chelsea L. Reinhard; Emily McCobb; Darko Stefanovski; Claire R. Sharp (Animals, 2020)
Upper respiratory tract disease (URTD) is a clinically relevant infectious disease in shelter cats, with individual and population-level welfare implications. The purpose of this study was to evaluate the effectiveness of famciclovir in reducing clinical signs of URTD in shelter cats during a therapeutic period of up to 21 days. Cats at two Northeastern United States animal shelters with URTD clinical signs were enrolled in a pragmatic, prospective, randomized, placebo-controlled clinical trial. Cats received either famciclovir (n = 11, target dose range 40–90 mg/kg) or placebo (n = 11), administered orally twice daily for up to 21 days with once-daily clinical scoring. At enrollment, conjunctival and oropharyngeal samples were collected for respiratory pathogen identification by RT-PCR. Zero-inflated Poisson regression was used to evaluate the treatment group effects and changes in clinical scoring over time. With each day of treatment, cats in both groups were less likely to experience worsening clinical scores; however, the risk of worsening scores with each day of treatment was significantly less in the famciclovir group compared to placebo (p = 0.006). Feline herpesvirus (FHV-1) DNA was detected in 11/21 cats. The findings justify further pragmatic studies to determine whether famciclovir treatment can contribute to a clinically relevant reduction in URTD morbidity in shelter cats.